Interaction of genetic risk score (GRS) and Plant-Based diet on atherogenic factors and body fat distribution indices among women with overweight and obesity: a cross-sectional study - Mahya Mehri Hajmir; Atieh Mirzababaei; Faezeh Abaj; Yasaman Aali; Mahsa Samadi; Khadijeh Mirzaei (Scientific Reports)
Abstract The association between plant-based diets, obesity, cardiovascular disease (CVD), and genetic predisposition is still not fully understood. This study explored how plant-based diets interact with genetic susceptibility to atherosclerosis and body fat in 377 Iranian women aged 18 to 48 who were overweight or obese. Using a validated 147-item food frequency questionnaire (FFQ), we established three plant-based diet indices: the Plant-Based Diet Index (PDI), the Healthy Plant-Based Diet Index (hPDI), and the Unhealthy Plant-Based Diet Index (uPDI). We calculated a Genetic Risk Score (GRS) based on three body mass index (BMI)-related single nucleotide polymorphisms (SNPs) and analyzed its interaction with the PDI. Results showed that tertile 2 of the PDI had a significant negative interaction with moderate and high-risk alleles on key atherogenic factors, including the atherogenic index of plasma (AIP), triglyceride glucose (TyG), lipid accumulation product (LAP), and visceral adiposity index (VAI) (P < 0.05). A borderline negative interaction between tertile 2 of the hPDI and moderate risk alleles regarding the Body Shape Index (ABSI) was also observed (P = 0.05). Conversely, tertile 2 of the uPDI had a significant positive interaction with moderate risk alleles related to both the Castelli Risk Index I (CRI.I) and II (CRI.II) (P = 0.03). This study suggests that interactions between genetic susceptibility and plant-based diet indices are linked to atherogenic factors and body composition.